2022
DOI: 10.1002/jcla.24803
|View full text |Cite
|
Sign up to set email alerts
|

Serum brain‐derived neurotrophic factor in coronary heart disease: Correlation with the T helper (Th)1/Th2 ratio, Th17/regulatory T (Treg) ratio, and major adverse cardiovascular events

Abstract: Background Brain‐derived neurotrophic factor (BDNF) exerts protective roles against dyslipidemia, atherosclerosis, and inflammation in cardiovascular diseases; meanwhile, it retards CD4+ T cell differentiation into T helper (Th)1 and Th17 cells. Hence, this study aimed to investigate the linkage of serum BDNF with Th1/Th2 ratio, Th17/regulatory T (Treg) ratio, and major adverse cardiovascular events (MACE) risk in the coronary heart disease (CHD) patients. Methods This prospective study detected serum BDNF in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Direct interactions may also occur in the bloodstream. It has been reported that serum BDNF levels negatively correlate with the Th1/Th2 ratio and Th17/Treg ratio in patients with cardiovascular diseases [76]. Furthermore, it has been suggested that BDNF can increase T cell proliferation and influence the differentiation of T cells into various subsets [77].…”
Section: The Interaction Between Cd4+ and Bdnfmentioning
confidence: 99%
“…Direct interactions may also occur in the bloodstream. It has been reported that serum BDNF levels negatively correlate with the Th1/Th2 ratio and Th17/Treg ratio in patients with cardiovascular diseases [76]. Furthermore, it has been suggested that BDNF can increase T cell proliferation and influence the differentiation of T cells into various subsets [77].…”
Section: The Interaction Between Cd4+ and Bdnfmentioning
confidence: 99%